Characterization of Electronic States of Volatile Anaesthetics by Electron Energy Loss Spectroscopy and Synchrotron Radiation - Lange, Emanuele (2019)
Volatile anaesthetics are widely used in clinical practice to induct and maintain anaesthesia through inhalation. The major atmospheric effects that may arise from emission of volatile anaesthetics are their contributions to ozone depletion in the stratosphere and to greenhouse global warming. In this thesis we present spectroscopic studies on UVradiation and electron interaction with three of the volatile anaesthetics currently in use, sevoflurane (C4H3F7O), isoflurane (C3H2ClF5O) and halothane (C2HBrClF3), in order to comprehensively describe the underlying molecular mechanisms of these molecules yielding dissociation. Electron scattering elastic differential cross sections (DCS) by the three mentioned molecules were measured for energies from 8.0 eV to 50 eV. The experimental DCSs and integral cross sections (ICSs) were compared with theoretical calculations, performed by collaborating groups, using two different methodologies, the Schwinger multichannel method (SMC) and the independent atom model–screening corrected additivity rule (IAM-SCAR). Moreover, we present, for the same compounds, results from VUV photoabsorption measurements over the wavelength range 115-220 nm, together with ab initio theoretical calculations of the vertical excitation energies and oscillator strength. This combined experimental and theoretical study allows a comprehensive description and characterization of the electronic states of these chemical compounds. The measured photoabsorption cross sections were also used to calculate the photolysis lifetime of the molecules in the Earth’s atmosphere from ground level up to the limit of the stratopause.